A different shade of colonialism : Egypt, Great Britain, and the mastery of the Sudan - Powell, Eve Troutt (Colonialisms, 2003)
This incisive study adds a new dimension to discussions of Egypt's nationalist response to the phenomenon of colonialism as well as to discussions of colonialism and nationalism in general. Eve M. Troutt Powell challenges many accepted tenets of the binary relationship between European empires and non-European colonies by examining the triangle of colonialism marked by Great Britain, Egypt, and the Sudan.